Analiza działań politycznych Wielkiej Brytanii wobec Mandatu Palestyny - Krzaczek, Michał (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
One of the causes of the Israeli-Arab conflict is the policy of United Kingdom towards trusteeship mandate on historical Palestine land in the 1920-1948 years. Analysis of political directions British empire appears significant to understand the essence of a cultural, religious and political tension of dispute. An inseparable element of the study is also characteristic of the political stances of British decision-makers and proposed by them solutions, which would end the growing conflict. By remarking on the above elements, the author suggests a division of the period of exercising power by the Europeans, depending on directions United Kingdom’s policy. The present article al so states a broad analysis of political actions towards the population of Jewish and Muslims, who lived in Mandate lands in trusteeship time.
Keywords: Mandate for Palestine; United Kingdom’s politic; Jewish-Arab conflict; international relations; ethnic conflict